Ileamatologic Malignancy Trends in Incidence at NORIN Cancer Hospital Nawabshah-SBA - Sardar Khatoon Chandio, Mujahid Ali Chandio, Kousar Parveen, Qatvar Rana Brohi, Ghularn Asghar Chandio, Bharat Lai , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To study the different trends in incidence of hematological malignancies IHM) in divided decades oflife from interior of Sindh province. Methods: This cross sectional. convenient study was carried out at Oncology department, NORIN Cancer Hospital. Total 885 patients from different cities of Sindh diagnosed as hematological malignancy were included. The duration of study was from October 2012- March 2018, 5 years and five months period. All cases were entered into excel and analyzed by SPSS 20. All the patients' data were recorded after the written permission of Ethical Review Committee, NORIN Cancer Hospital Nawabshah. Results: The total number of patients registered with various hematological malignancy were 885 during 2012-2019. Lymphoma combined NHL and HL (Non-Hodgkin Lymphoma and Hodgkin Lymphoma) were 522( 59%) of total Hl & fol lowed by Leukemia combined were 333(38%), and Plasma cell neoplasm the Multiple Myeloma represent the 30(3%). The male predominance is noticed in every category. NHL is more prevalent in pediatric aroup. while1-1L is more prevalent in adults and middle age groups. Conclusion: Thee most common hematologic malignancy in adults were H L and NHL, followed by Leukemia. Lymphoid than Myeloid, and Multiple Myeloma. All the categories are represented with male predominance. In pediatric Cage group, the NHL. is more prevalent.